Peran Desentralisasi Fiskal Terhadap IPM dan Penyerapan Tenaga Kerja di Kota Jambi - Ahmad Soleh; Ayu Ardilla (PARETO : Jurnal Ekonomi dan Kebijakan Publik, 2019)
This study analyzes how the role of fiscal decentralization on economic growth, the human development index and direct and indirect employment absorption that occurred in Jambi City. We applied descriptive qualitative and quantitative methods. The results of the study show: 1) The average degree of fiscal decentralization in Jambi City is 12.11 percent and is included in the less criteria. 2). There is a negative and insignificant influence between the degree of fiscal decentralization on economic growth in Jambi City. 3). Based on the direct impact, the degree of fiscal decentralization has a positive and not significant impact on the temporary HDI towards the absorption of positive and significant workforce. 4) Based on the impact indirectly the degree of fiscal decentralization has a positive and not significant effect on the development index and has a positive and not significant effect on employment.